Perspective of Chiral Colloidal Semiconductor Nanocrystals: Opportunity and Challenge - Gao, Xiaoqing; Han, Bing; Yang, Xuekang; Tang, Zhiyong (Journal of the American Chemical Society, 2019)
Chiral colloidal semiconductor nanocrystals (NCs) are an emerging type of chiral materials. These chiral NCs exhibit unique quantum confinement-determined optical activity and have aroused much interest in the multidisciplinary fields of chemistry, physics and biology. Herein, the state-of-the-art progresses of their rational synthesis, fundamental understanding and potential application are summarized. In addition, a personal view about the future development of chiral semiconductor NCs is offered.